National Party Organizations and Party Brands in American Politics The Democratic and Republican National Committees, 1912-2016 - Heersink, Boris (Oxford University Press, Incorporated, 2023)
In this book, Boris Heersink analyzes the DNC and RNC in their role as party-branders. Specifically, he argues the main role of the committees is to try and promote an image of the party to voters in a way they hope will help them win elections. However, in doing so, they often have to make controversial decisions, such as picking sides in big intra-party fights about what policies to support and what voting groups to target or ignore. Through extensive historical analysis, this book shows that the DNC and RNC were part of every major American policy debate throughout the 20th century